A Dilemma Within Doctoral Supervision: Applying an Ethical Decision‐Making Model. Issue 2 (1st October 2021) - Chae, Nancy; Gosling, David R.; Goshorn, Jeremy R.; Fan, Shuhui
Abstract : This article is based on the second place–winning submission to the 2019 American Counseling Association Graduate Student Ethics Competition for Doctoral Degree Students. The fictional ethical dilemma presents three perspectives within doctoral supervision (i.e., a doctoral supervisor, supervisees, and faculty supervisor) related to grappling with master's‐level school counseling supervisees. A selected ethical decision‐making model is used to delineate the problems and dimensions of the dilemma and offer courses of action in response to the ethical dilemma. Implications for counselors, supervisors, and counselor educators are discussed.